2010
DOI: 10.2174/092986710792065063
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-Spectroscopy: A Non-Invasive Tool for Medical Diagnostics and Drug Analysis

Abstract: Constant development enabled Infrared (IR) spectroscopy to become a widely used, non-invasive tool for fast sample analyses with less to no pre-preparation. Furthermore, computational data handling is no more a limiting factor and hence, IR measurements are predestined for clinical diagnostics and drug analysis. Within this review the focus was put on clinical topics of high interest. One example is Alzheimer's disease, where the exact metabolism is still not clarified, or blood glucose monitoring for high thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…FTIR spectroscopy has already been used in medical diagnostics for some diseases as an alternative to well-known biochemical and histochemical methods and it is suitable for routine use. 28,29 The present study was a complementary investigation to our ongoing proteomic analyses of GD and allowed us to carry our reserarch from the proteomic level to metabolomics in the biology systems frame. We attempted to introduce and apply FTIR spectroscopy to make molecular characterization of GD and our results showed that the application of this technique in GD research deserves further investigation to assess its potential in the diagnosis and monitoring of GD.…”
Section: Discussionmentioning
confidence: 98%
“…FTIR spectroscopy has already been used in medical diagnostics for some diseases as an alternative to well-known biochemical and histochemical methods and it is suitable for routine use. 28,29 The present study was a complementary investigation to our ongoing proteomic analyses of GD and allowed us to carry our reserarch from the proteomic level to metabolomics in the biology systems frame. We attempted to introduce and apply FTIR spectroscopy to make molecular characterization of GD and our results showed that the application of this technique in GD research deserves further investigation to assess its potential in the diagnosis and monitoring of GD.…”
Section: Discussionmentioning
confidence: 98%
“…However, some critical aspects can restrict its use, including the cost of analytical testing and in some cases the long waiting time between the sampling and return of analysis results. Human studies have demonstrated the potential of infrared spectroscopic methods for reliable clinical chemistry [ 11 , 12 ], as well as clinical applications and diseases diagnosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[22] These modes serve as fast, precise indicators for detecting active components and their distribution in pharmaceutical drug development and production. [23] The chemical structure dictates the biologically relevant properties of molecules. Therefore, vibrational signatures have been identified to probe the structure of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating vibrational modes is also useful for identifying drug‐binding sites [22] . These modes serve as fast, precise indicators for detecting active components and their distribution in pharmaceutical drug development and production [23] . The chemical structure dictates the biologically relevant properties of molecules.…”
Section: Introductionmentioning
confidence: 99%